A work of heart : understanding how God shapes spiritual leaders - McNeal, Reggie; McNeal, Reggie (San Francisco : Jossey-Bass, 2000)
Publisher's description: Spiritual leaders must become experts in matters of the heart. They must learn to discern God at work in their own lives, shaping their hearts to embrace the particular ministries to which they are called. A Work of Heart shows how God prepares leaders today just as he did in biblical times-and how God creates these leaders in order to share his heart with his people.
Introduction : Looking for God in all the right places -- pt. 1. How God shaped Moses, David, Paul, and Jesus for leadership. Moses : a heart on a mission -- David : a heart after God -- Paul : a heart captured by God -- Jesus : the heartbeat of God -- pt. 2. Recognizing God's shaping work in our own lives. Culture : meeting the world -- Call : figuring out why we are here -- Community : connecting with others' hearts -- Communion : rehearsing for eternity -- Conflict : learning to die so we can live -- Commonplace : discovering that the ordinary is extra-ordinary -- Conclusion : Collaborating with God's heart-shaping project.
Includes bibliographical references (page 193) and index.
Keywords: Christian leadership